(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ANNOTATION: In order to better understand how writers depict the attraction, corruption, and fallout from these ideas and opinion, this article looks at the themes of money and power in contemporary literature. The author talks on how characters in modern fiction are lured to the prospect of material prosperity and social standing, only to encounter problems along the way, such as deceit, greed, and moral ambiguity. Furthermore emphasized is the corrupting effect of money and power, illustrating how those who achieve significant success frequently experience social isolation, moral degradation, and a loss of humanity.